2011
DOI: 10.2298/jsc100505036p
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater canal Vojlovica, industrial complex Pancevo, Serbia: Preliminary ecotoxicological assessment of contaminated sediment

Abstract: 460 PLANOJEVIĆ et al. diment risk assessment procedures integrates the effects of multiple stressors and gives a realistic insight into not only sediment contamination by toxic pollutants, but also the sediment status in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Although M. aquaticum is a candidate for an additional species in refined risk assessment, toxicity data concerning the sensitivity of this species is scarce and available recovery data is largely nonexistent. The sediment contact tests with M. aquaticum 12 have been implemented in several case studies 29–31. Although the test protocol has been suggested for spiked sediment toxicity tests as well, no results of such studies (if any) have been published thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Although M. aquaticum is a candidate for an additional species in refined risk assessment, toxicity data concerning the sensitivity of this species is scarce and available recovery data is largely nonexistent. The sediment contact tests with M. aquaticum 12 have been implemented in several case studies 29–31. Although the test protocol has been suggested for spiked sediment toxicity tests as well, no results of such studies (if any) have been published thus far.…”
Section: Introductionmentioning
confidence: 99%
“…This channel was built in 1962 to collect the wastewater discharges from the industrial complex of Pančevo city (Figure 2). The industrial complex consists of a chemical fertilizer factory, a petrochemical factory, and an Oil Refinery [32,33]. Within the petrochemical factory is a wastewater treatment plant designed to accept and process wastewater from all Petrochemical production plants and from the Oil Refinery and its effluent waste is discharged to the wastewater channel.…”
Section: Methodsmentioning
confidence: 99%
“…The conclusion was that key toxicants causing plant growth inhibition in the sample must have been herbicides undetectable by chemical screening due to fast degradation. Studies of Stešević et al [43] and Planojević et al [44] attributed high inhibitions of M. aquaticum growth to very high concentrations of metals. It seems that M. aquaticum is sensitive to sediment contamination by trace metals and herbicides, but less sensitive to non-polar organic pollutants [13,[42][43][44].…”
Section: Test Of Natural Sedimentsmentioning
confidence: 98%
“…Studies of Stešević et al [43] and Planojević et al [44] attributed high inhibitions of M. aquaticum growth to very high concentrations of metals. It seems that M. aquaticum is sensitive to sediment contamination by trace metals and herbicides, but less sensitive to non-polar organic pollutants [13,[42][43][44]. Feiler et al [15] applied a test battery consisting of five sediment contact tests (including the M. aquaticum test) and concluded that the chemical contamination of the tested sediments was in general proved by the test battery, but not by every single toxicity test applied in each sample.…”
Section: Test Of Natural Sedimentsmentioning
confidence: 98%